IMPLEMENTASI PROGRAM REDESAIN TATA TERTIB PERPUSTKAAAN DI SMA NEGERI 3 KOTA SERANG - Yayah Haryati (Tarbawi, 2017)
This study aims to describe the plan, implementation, obstacles and redesain results of library discipline in SMA Negeri 3 Serang City. Data collection techniques through observation, interviews, and documentation. Data analysis uses data reduction measures, data displays, and conclusions. The result of the research shows: 1) redesign planning of library discipline is good enough, it contains about how to use library materials, how many books can be borrowed, how long time of lending, who can use library, and sanction; 2) preparing materials for redesigning design, writing design and tatatertib and writing drawings, printing designs on banners, and finally installing or attaching the order and slogans to predetermined walls, corners or locations; 3) the place of placement of the order takes the stand in the unused living room; and 4) the results of redesigning the discipline and slogans in the library is good enough, seen in the view of the writing-shaped library rules illustrated color and image, followed by the making of slogans in writing form with illustrations of images and colors contains the himbaun to comply with and implement the orderly food of libraries and what librarians should and should do. Keywords. Library, Discipline, Code of Conduct.